Odpowiedzi

2009-11-29T12:59:53+01:00
A) 27- x =35 x= 35 - 27 x-=8
b) -0,5x =12 -x = 24 x = -24
c) 3x -4 =11 3x = 11+4 3x= 15 x= 5
d) 8x= 18,4+6x 2x = 18,4 x= 9,2
e)-5x-17=-9x+3 -5x+9x = 3+17 4x = 20 x=5
f)7x+2=5+4x+9 3x = 12 x= 4
g)2(x-3)+3(4-x)=5 2x-6+ 12-3x=5 -x+6=5 -x=-1 x=1
h)2(x+4)-5(x+3)=2 2x+8-5x-15=2 -3x -7= 2 -3x=9 x=-3
1 5 1
2009-11-29T13:03:48+01:00
A)27-x=35
-x=35-27
-x=8/*(-1)
x=-8
b)-0,5x=12/:(-0,5)
x=-24
c)3x-4=11
3x=11+4
3x=15/:3
x=5
d)8x=18,4+6x
8x-6x=18,4
2x=18,4/:2
x=9,2
e)-5x-17=-9x+3
5x+9x=3+17
14x=20/:14
x=20/14
x=0,7
f) 7x+2=5+4x+9
7x-4x=5+9-2
3x=12/:3
x=4
g) 2(x-3)+3(4-x)=5
2x-6+12-3x=5
2x-3x=5+6-12
-x=-1*(-1)
x=1
h) 2(x+4)-5(x+3)=2
2x+8-5x-15=2
2x-5x=2-8+15
-3x=9/:(-3)
x=-3